Relationship between concomitant atopic diseases with atopic dermatitis severity and persistence / Goh Siew Wen ... [et al.] - Goh, Siew Wen; Jamil, Adawiyah; Lee, Choon Sian; Arumugam, Mohan (Faculty of Medicine, 2021)
Introduction: The atopic march consists of atopic dermatitis (AD), allergic rhinitis or sinusitis (AR), allergic conjunctivitis (AC) and bronchial asthma (BA). The influence of concomitant atopic diseases on AD is under-explored. We determined the relationship between personal and family history of atopic diseases with AD severity and persistence. Methods: A cross sectional study involving AD patients was performed at dermatology clinics of two tertiary hospitals. Inclusion criterion was all patients diagnosed with AD. Demographic data, personal and family history of atopy (BA, AR and AC) were obtained by face-to-face interview. AD severity was evaluated using Investigator's Global Assessment (IGA). AD was considered persistent if continued beyond age 12 years. Results: Sixty patients aged 21.6±17.2 participated. There were 25(41.7%) with concomitant AR, 16(26.7%) BA and 12(20%) AC. Forty seven (78.3%) patients had family history of atopy, 25(41.7%) had eczema, 24(40%) AR, 19(31.7%) BA and 2(3.3%) AC. Patients with BA [OR=3.8, 95%CI 1.04 to 14.4)], BA and AR [OR=9.74, 95%CI 1.13 to 83.67) and family history of BA [OR= 4.00, 95%CI 1.20 to 13.27) were more likely to exhibit moderate-severe AD. Personal AR, AC and family history of AD and BA were significantly more prevalent in patients with persistent AD. Conclusions: AR was the most common atopic disease associated with AD. Family history of eczema and AR were common. Personal BA, BA with AR and family history of BA were predictors of severe AD. Personal AR, AC and family history of AD and BA were associated with AD persistence.